PEMAHAMAN PERATURAN MENTERI NEGARA AGRARIA/KBPN NO. 1 TAHUN 1999 TENTANG TATA CARA PENANGANAN SENGKETA PERTANAHAN - Sholat, Junaidi; Apriandani, Babby; Manurung, Julpan Hartono SM; Maharani, Karina Putri; Sirait, Kiki Adha (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The mandate of agrarian reform in Indonesia was further strengthened through the Decree of the People's Consultative Assembly (MPR) Number IX/MPR/2001, which regulates agrarian reform and natural resource management. This demonstrates that agrarian reform aims not only for the physical distribution of land but also for strengthening natural resource management to provide maximum benefits to the community. Furthermore, through the Decree of the People's Consultative Assembly (MPR) Number 5/MPR/2003, the UUPA, along with its implementing regulations, aims to ensure legal certainty for land rights throughout the Republic of Indonesia. Legal disputes arise from objections to claims regarding land rights, whether regarding land status, priority, or ownership, with the hope of obtaining administrative resolution in accordance with applicable provisions. Regulation of the Minister of State for Agrarian Affairs/National Land Agency Number 1 of 1999 concerning Procedures for Handling Land Disputes, defines the dispute. Keywords: Agrarian, Dispute Abstrak: Mandat reforma agraria di Indonesia semakin dipertegas melalui Ketetapan MPR RI Nomor IX/MPR/2001 yang mengatur pembaruan agraria dan pengelolaan sumber daya alam. Hal ini menunjukkan bahwa reforma agraria tidak hanya bertujuan untuk distribusi fisik tanah, tetapi juga memperkuat pengelolaan sumber daya alam agar dapat memberikan manfaat maksimal kepada masyarakat. Selain itu, melalui Keputusan MPR RI Nomor 5/MPR/2003. UUPA dengan seperangkat peraturan pelaksanaannya, bertujuan untuk terwujudnya jaminan kepastian hukum terhadap hak-hak atas tanah diseluruh wilayah Republik Indonesia. Munculnya sengketa hukum merupakan berawal dari keberatan dari tuntutan suatu hak atas tanah baik terhadap status tanah, prioritas maupun kepemilikannya dengan suatu harapan mendapatkan penyelesaian administrasi sesuai dengan ketentuan yang berlaku. Peraturan Menteri Negara Agraria/Badan Pertanahan Nasional Nomor 1 Tahun 1999 tentang Tata Cara Penanganan Sengketa Pertanahan, yang dimaksud dengan sengketa. Kata kunci: Agraia, Sengketa